Independent control of organ number and distribution pattern in rice panicle - Yamamoto, Eiji; Yabe, Shiori; Inari-Ikeda, Mayuko; Yoshida, Hideki; Morinaka, Yoichi; Matsuoka, Makoto; Kitano, Hidemi (Frontiers in Plant Science, 2023)
As the determinants of yield products, rice panicle traits are important targets for breeding. Despite their importance in grain filling and subsequent yield productivity, knowledge on the organ distribution pattern in rice panicles is limited owing to the lack of objective evaluation methods. In this study, we developed a method for quantifying rice panicle organ distribution patterns. To validate our method for practical application in biology, we integrated this method into a quantitative trait locus (QTL) analysis and identified QTLs for panicle organ distribution patterns in rice. Interestingly, Grain number 1 (Gn1), a major QTL of organ number, was not identified as a QTL for distribution pattern, indicating that the number and distribution of panicle organs are independently controlled. This study provides insight into rice panicle organ distribution patterns that will help improve breeding targeting rice panicle architecture.